Similar Physical Modeling of Roof Stress and Subsidence in Room and Pillar Mining of a Gently Inclined Medium-Thick Phosphate Rock - Xiaoshuang Li; Zhifang Liu; Shun Yang (Advances in Civil Engineering)
Gently inclined medium-thick orebodies are generally recognized as the most difficult type of orebody to mine, using current available strategies (i.e., the room and pillar method). In the present study, a similar physical model was used to investigate the roof stress and subsidence for mining gently inclined medium-thick phosphate rock from the Jinning Phosphate Mine, Yunnan Province, China. The stress field, displacement field, and roof failure evolution characteristics of the surrounding rock with stope structures of 3 m, 5 m, or 8 m ore pillars were considered. The results showed that, after mining stopped, obvious pressure relief areas formed above the three stope structures, and pressure-bearing areas formed at the front of the roof. With extending the mining in the working face, the stress relief boundary also gradually increased, and the top of the roof tended to sink with a maximum subsidence of –14.58 mm, –4.67 mm, and –3.48 mm. Due to the mining activity, the overlying strata bent and subsided from top to bottom, creating bending subsidence, fracture, and caving zones.